2012
DOI: 10.1021/ac203447k
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Determination of a Low-Concentration Active Ingredient in Pharmaceutical Tablets by Backscatter and Transmission Raman Spectrometry

Abstract: A total of 383 tablets of a pharmaceutical product were analyzed by backscatter and transmission Raman spectrometry to determine the concentration of an active pharmaceutical ingredient (API), chlorpheniramine maleate, at the 2% m/m (4 mg) level. As the exact composition of the tablets was unknown, external calibration samples were prepared from chlorpheniramine maleate and microcrystalline cellulose (Avicel) of different particle size. The API peak at 1594 cm(-1) in the second derivative Raman spectra was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 44 publications
(118 reference statements)
2
11
0
Order By: Relevance
“…38 Their results contradict the later findings of Townshend et al, that quantitative assessment with transmission Raman spectroscopy was more sensitive to a mismatch in particle size of the filler between the calibration and test sets than was Raman spectroscopy in backscatter geometry. 34 The present study confirms that transmission Raman spectroscopy is indeed sensitive to variations in the particle size of the drug substance and of the filler, as well as of other matrix effects, such as tablet hardness (here expressed as compression force). We believe that in backscatter mode, the effect of sampling volume is a statistical phenomenon related to the number of particles of the drug substance.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…38 Their results contradict the later findings of Townshend et al, that quantitative assessment with transmission Raman spectroscopy was more sensitive to a mismatch in particle size of the filler between the calibration and test sets than was Raman spectroscopy in backscatter geometry. 34 The present study confirms that transmission Raman spectroscopy is indeed sensitive to variations in the particle size of the drug substance and of the filler, as well as of other matrix effects, such as tablet hardness (here expressed as compression force). We believe that in backscatter mode, the effect of sampling volume is a statistical phenomenon related to the number of particles of the drug substance.…”
Section: Resultssupporting
confidence: 81%
“…Investigations of the influence of particle size in the literature have shown a varying degree of sensitivity to variation in particle size, although it has been suggested that transmission Raman is more sensitive than backscatter Raman owing to the significantly longer optical path length. 34 Their suggestion, however, is not in agreement with the findings of Hu et al, 38 who concluded that if the sampling volume is much larger than the particle size, the Raman signal intensity should not be affected by particle size. A proposed method for handling sensitivity to particle size in quantitative Raman analysis is simply to make sure that calibrations are made on a size range relevant to the actual samples.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations